Harnessing a knowledge worker’s competency: Lessons from the software development teams - Shukla, Manasi (2004)
In this conceptual paper, we propose that the work force can no longer be understood only as a factor of production, but must be projected as a strategic core competency of any organization. The “knowledge-based”, post-industrial economy has lead to a higher degree of pressure on the corporations to nurture and enhance their key strategic resource viz. the Knowledge worker(K-worker). Based on the resource based view and firm strategy, we hereby define the core human competency of the K-worker as a firm specific, rent-generating resource manifested in the behavior pattern of its employees that is aligned with a firm’s core business activities. Besides, our literature survey of the software developer’s field suggests the key business imperatives of future orientation, customer orientation, team work, problem resolution and quality. Hence, these five are hypothesized as the key human competency determinants of a software developer or a K-worker.Thus, our novel approach presupposes that the human competency grows with and around the key business activities of a business organization. The utility of this approach is projected through the lens of the systems view via the fifth discipline and integrated with the quality management practices to build a bulwark for the nurturing of human core competencies. At the heart of this systemic thinking is a shift of mind better termed as “metanoia”.We thus emphasize that k-worker management needs a more individualized and customized appreciation unlike what has been the norm so far.This strategic human competency approach is then the crucial ground for a learning enabled organization of the future that is struggling under enormous pressure of competition in today’s landscape.